WordPress plugin development cookbook : explore the complete set of tools to craft powerful plugins that extend the world's most popular CMS - Lefebvre, Yannick (Packt Publishing, 2022)
WordPress is one of the most widely used, powerful, and open content management systems (CMSs). Whether you're a site owner trying to find the right extension, a developer who wants to contribute to the community, or a website developer working to fulfill a client's needs, learning how to extend WordPress' capabilities will help you to unleash its full potential. This book will help you become familiar with API functions to create secure plugins with easy-to-use administration interfaces. This third edition contains new recipes and up-to-date code samples, including new chapters on creating custom blocks for the block editor and integrating data from external sources. From one chapter to the next, you'll learn how to create plugins of varying complexity, ranging from a few lines of code to complex extensions that provide intricate new capabilities. You'll start by using the basic mechanisms provided in WordPress to create plugins, followed by recipes covering how to design administration panels, enhance the post editor with custom fields, store custom data, and even create custom blocks. You'll safely incorporate dynamic elements into web pages using scripting languages, learn how to integrate data from external sources, and build new widgets that users will be able to add to WordPress sidebars and widget areas. By the end of this book, you will be able to create WordPress plugins to perform any task you can imagine.